Islamophobia and International Peace: A Critical Discourse Analysis of Religious and Political Themes of Imran Khan’s Speeches at United Nations General Assembly as Prime Minister of Pakistan - Javeed, Muhammad Farooq; Fayyaz, Shafaq (Journal of Ecohumanism, 2025)
This study critically examines Imran Khan's speeches at the United Nations General Assembly (UNGA) from 2019 to 2021, focusing on his discourse surrounding Islamophobia and its implications for international relations. Utilizing Fairclough’s three-dimensional model and Paul Gee’s seven building blocks of discourse, the research analyzes the linguistic and strategic elements of Khan's rhetoric. The findings reveal that Khan frames Islamophobia as a systematic global issue, advocating for cultural exchange and mutual understanding while countering anti-Islamic narratives. His speeches emphasize the need for recognition of Muslim rights and challenge misconceptions about Islam, portraying it as a peaceful and united faith. This analysis highlights the intersection of religious identity and political strategy in Khan's discourse, positioning Pakistan as a moral actor in the global arena. The study contributes to the understanding of how political leaders utilize language to address complex religious and political issues and combat prejudice at international forums.